Effects of activation temperature on densities and volumetric CO2 adsorption performance of alkali-activated carbons. (15th February 2019) - Li, Dawei; Zhou, Jiaojiao; Wang, Yu; Tian, Yuanyu; Wei, Ling; Zhang, Zongbo; Qiao, Yingyun; Li, Junhua
Highlights: Effect of alkali activation temperature on densities of ACs was reported. Effect of alkali activation temperature on ACs' volumetric CO2 capture capacity was studied. ACs' true density was dominated by atomic carbon ratio, not by graphitization degree. ACs fit for practical CO2 capture should be judged by volumetric capture performance. Abstract: Activated carbons (ACs) prepared by chemical activation were promising materials for CO2 capture, but how to adjust their densities and volumetric CO2 adsorption performance is unclear. We prepared ACs from petroleum coke by KOH activation to study impacts of activation temperature (540–820 °C) on densities and volumetric CO2 adsorption performance of ACs. As the activation temperature increased, the true density rose whereas the apparent density and tap density decreased. The true density of ACs was dominated by aromatic-carbon ratio, not by the previously-believed graphitization degree. The activation temperature required to achieve the maximum volumetric low-pressure CO2 uptake was lower than that needed to attain the highest gravimetric value (540 °C < 610 °C). When an AC was expected to display a high volumetric CO2 adsorption capacity, its tap density and gravimetric CO2 uptake should be moderate at least. The volumetric CO2 /N2 selectivity decreased with increasing activation temperature, mainly because of widening of micropore size distribution. This study provided new insights into ACs' densities, and highlighted judging ACs for CO2 capture by the previously-overlooked volumetric adsorption performance rather than only by the commonly-used gravimetric performance.